The Influence of Information Systems and Employee Competence on Service Effectiveness with Employee Performance as a Mediating Variable - Prajudy, Sugeng; Qomariyah, Nurul; Martini, Ni Nyoman Putu (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2024)
Law Number 25 of 2009 Concerning Public Services Article 1 Paragraph (1) states that public services are activities or series in order to fulfill service needs in accordance with laws and regulations for every citizen and resident for goods, services, and/or administrative services provided by public service providers. Service standards are benchmarks used as guidelines for service delivery and references for assessing service quality as obligations and promises of providers to the community in order to provide quality, fast, easy, affordable, and orderly services. The purpose of this study was to determine directly and indirectly the influence of information systems and competencies on effectiveness with employee performance as a mediating variable at the UPTD Motor Vehicle Testing Service of the Jember Regency Transportation Service. The number of samples in this study was 199 respondents. The analysis technique used was the Structural Equation Model (SEM) using the WarpPLS 7.0 application. The results of the data analysis showed (1) the information system variable had a positive but not significant effect on employee performance and competency directly had a significant positive effect on employee performance. (2) Information system variables have no significant effect on service effectiveness, but performance competence, employee performance directly has a significant positive effect on service effectiveness. (3) Information system variables and competence indirectly have a positive but insignificant effect on service effectiveness through employee performance.